1989
DOI: 10.1002/jemt.1060110202
|View full text |Cite
|
Sign up to set email alerts
|

Calibration methods for quantitative image processing in electron microscopy

Abstract: An image can be represented digitally as a matrix of numbers. When those numbers are linearly related to a property of the object, such as mass per unit area, a simple integration of an image area leads to a total of that property, such as the mass of a particle that is represented in a selected area. Following techniques pioneered by Bahr and Zeitler, we illustrate the use of photographic densitometry of films exposed in an electron microscope to measure electron scattering. The transmission of an electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Subsequently, Lamvik and Davilla (1989) showed that path length through standard particles, such as polystyrene spheres of known constant density, could be used to confirm directly the accuracy of the mass density measurements in images of particles recorded on film. By integrating intensities in the digitized film along different path lengths through the spheres, the mass could be determined, as long as the film density was within the linear intensity response region.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Lamvik and Davilla (1989) showed that path length through standard particles, such as polystyrene spheres of known constant density, could be used to confirm directly the accuracy of the mass density measurements in images of particles recorded on film. By integrating intensities in the digitized film along different path lengths through the spheres, the mass could be determined, as long as the film density was within the linear intensity response region.…”
Section: Introductionmentioning
confidence: 99%
“…The pixel values were either reversed (black to white and vice versa) or adjusted for maximum clarity and a smooth filtering function applied. These and other image processing algorithms and functions are very valuable means of removing noise and dirt ithat usually find their way into images (Fermin et aL, 1992;Hawkes, 1988;Lamvik and Davilla, 1989). The processed image was "dumped directly from the video screen to the Polaroid video recorder and printed on color paper.…”
Section: Image Processingmentioning
confidence: 99%